ANALYSIS OF SIM-RS USE IN OUTPAGE WITH HOT-FIT METHOD IN HOSPITAL - Nurhayati, Asti; Enggar Pramudita Wijayanti; Dinda Nur Wijayanti (Jurnal EduHealth, 2022)
Hospital Management Information System (SIMRS) is a system that provides information to support decision making. The organizational need for an integrated SIMRS implementation is very important as a tool or tool for measuring organizational performance, so there is a need for reports for hospital management according to the needs that underlie responsive, innovative, transparent, effective, and efficient organizations as a monitoring tool in measurable implementation. SIMRS is useful in improving the performance of hospitals in terms of speed of decision making in formulating strategies. The use of SIMRS operationally is useful for improving performance and services, facilitating coordination between units, increasing HR capabilities. The HOT Fit model places important components in the information system, namely humans (humans), organizations (organizations), and technology (Technology). The three factors in the HOT-Fit method are related in eight dimensions of the relationship for successful implementation, namely System Quality, Information Quality, Service Quality, System Use, User Satisfaction, Organizational Structure, Organizational Environment and net benefits. The purpose of this study is to analyze how the use of SIM-RS in outpatient units using the HOT-FIT method. The research method used is quantitative research. The instrument used in this study used a questionnaire. The results of this study indicate that the SIM-RS is useful in supporting services to patients. The SIM-RS used is quite good, judging from the indicators of human, organization, technology, user knowledge, regulations and benefits.